2008
DOI: 10.1007/s00438-008-0319-4
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements in Coffea (Gentianales: Rubiacea) transcripts and their role in the origin of protein diversity in flowering plants

Abstract: Transposable elements are major components of plant genomes and they influence their evolution, acting as recombination hot spots, acquiring specific cell functions or becoming part of protein-coding regions. The latter is the subject of the present analysis. This study is a report on the annotation of transposable elements (TEs) in expressed sequences of Coffea arabica, Coffea canephora and Coffea racemosa, showing the occurrence of 383 ESTs and 142 unigenes with TE fragments in these three Coffea species. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 89 publications
4
15
0
5
Order By: Relevance
“…2F), indicating the presence of substantially active TEs or TE fragments in maize seed development. Although it remains to be determined whether these NTRs have any biological function, some evidence has shown that TE-related regions are widely active and have acquired specific cell functions during their evolution (Vicient et al, 2001;de Araujo et al, 2005;Ohtsu et al, 2007;Lopes et al, 2008;Picault et al, 2009), and we did observe 46 TE-associated NTRs with EST evidence in addition to the support of our RNA-seq data (Fig. 2F).…”
Section: Discovery Of Ntrssupporting
confidence: 79%
“…2F), indicating the presence of substantially active TEs or TE fragments in maize seed development. Although it remains to be determined whether these NTRs have any biological function, some evidence has shown that TE-related regions are widely active and have acquired specific cell functions during their evolution (Vicient et al, 2001;de Araujo et al, 2005;Ohtsu et al, 2007;Lopes et al, 2008;Picault et al, 2009), and we did observe 46 TE-associated NTRs with EST evidence in addition to the support of our RNA-seq data (Fig. 2F).…”
Section: Discovery Of Ntrssupporting
confidence: 79%
“…These two retrotransposons were found to be common in species of Coffea and in Psilanthus ebracteolatus Hiern but with different activity rates, which has permitted the differentiation of species and accessions as well. Lopes et al (2008) annotated coding regions of ESTs and unigenes from Coffea arabica, C. canephora and C. racemosa, and suggested that many transposable element insertions involve diverse elements, such as LTR-retrotransposons, transposons, MITEs and Helitrons. In relation to LTRretrotransposons, representatives of Ty1-copia-like are preferentially inserted in the antisense orientation in the three species, while those of Ty3-gypsy-like are inserted in the sense orientation in C. arabica.…”
Section: Introductionmentioning
confidence: 99%
“…(11,17,18) Com o propósito de investigar em maiores detalhes as possíveis contribuições dos elementos móveis em sequências codificantes, foi realizada a busca por ESTs que validassem os modelos gênicos preditos que sugeriram a utilização de sequências de TEs na codificação de proteínas do genoma hospedeiro, possibilitando a análise mais rigorosa destes casos. Esta inspeção confirmou a ocorrência de TEs na região codificante de 4 genes ortólogos para C. reinhardtii (Figura 5.3) e 8 em V. carteri ( Figura 5.4).…”
Section: Resultsunclassified
“…O conhecimento acerca do potencial de TEs em eventos evolutivos, juntamente com o aumento do número de genomas sequenciados, tem incentivado o estudo da associação entre elementos de transposição e estruturas gênicas. (11,17,18,25) Quando genomas apresentam divergência recente, é esperado que características relativas ao conteúdo gênico dos mesmos -como número de genes e estrutura destes, a exemplo da organização de éxons e íntrons -permaneçam altamente conservadas. (56) Este fato é importante para estudos que almejam identificar modificações introduzidas por TEs, uma vez que estabelece um cenário adequado em que podem ser realizadas comparações de contextos gênicos.…”
Section: Genes Ortólogos E Associação Destes Com Tesunclassified
See 1 more Smart Citation